PROBLEMATIKA GURU DALAM PENERAPAN KURIKULUM MERDEKA BELAJAR DI SEKOLAH DASAR - Dhiya Sutrina; Putri Handayani; Wulandari Wulandari; M.Jaya Adi Putra; Mauliatun Nisa (EDUCATIONAL JOURNAL : General and Specific Research, 2024)
This research discusses the problems in implementing the Independent Learning Curriculum at Pekanbaru Technology Elementary School, with a focus on the obstacles faced by teachers in its implementation. Issues raised included limited supporting resources, difficulties in the process of adapting to the new curriculum, as well as obstacles in the assessment system, both formative and summative assessments. Research data was obtained through an interview with several teachers who was directly involved in implementing the Independent Curriculum at the school, where the interview was conducted using Google Forms. This research uses a qualitative approach with descriptive analysis methods, where the results of interviews are analyzed to identify the main obstacles that hinder curriculum implementation. The research results show that Pekanbaru Technology Elementary School faces a number of challenges, including limited project-based learning facilities, teachers' difficulties in designing flexible and innovative learning, and a lack of synchronization between formative and summative assessments. From these findings, it is recommended that schools increase resources and provide more intensive training to teachers, as well as develop more structured assessment strategies.